The Effect of Communicative Approach towards Students’ Reading Comprehension on The Eighth Grade of SMP PGRI 3 South Jakarta - Utami Utami; Doni Anggoro Ari Santoso (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The research aims at finding out the effect of Communicative Approach’s learning model to the students’ reading ability. The research was conducted at SMP PGRI 3 South Jakarta. The method applied was experimental research. Samples were taken randomly and grouped in two classes of experiment and control consisting of 30 students of each group. The analysis of data for hypothesis test was by using t-test. Prior to the calculation of hypothesis test, it was preceded by the calculation of normality test by applying Lilliefors and homogenity test with F-test. Findings show that for experiment class, Lcount = 0.1097 and Ltabel = 0.161, even controll class it is obtained Lcount = 0.1214 and Ltable = 0.161. if Fcount= 1.32 and Ftable=1,84. It can be concluded that both research groups are normally distributed and the data is homogenous with α = 0.05. the hypothesis test with t-test statistic formula, it is obtained that tcount is 2.46 and ttable is 1.67. After being compared, tcount value is somewhat higher than ttable value (2.46 > 1.67).